Tripolitania e Cirenaica; storia, geografia, usi e costumi. - Maria, Federico de (G. Brugnoli, 1911)
Keywords: Récits de voyage -- Djebel Nefousa; Tourisme -- Djebel Nefousa

Passeggiate sentimentali in Tripolitania; visioni di pace e di guerra - Maria, Federico de (G. Puccini, 1912)
Keywords: Récits de voyage -- Djebel Nefousa

La Tripolitania - Minutilli, Federico (Piccola biblioteca di scienze moderne, 1912)
Keywords: Récits de voyage -- Djebel Nefousa

Tripolitania - Nazari, Vittorio (Tip. Editrice Nazionale, 1911)
Keywords: Récits de voyage -- Djebel Nefousa

Il Viaggio Del Sovrano in Libia - Ravagli, Federico (Gli annali dell'Africa italiana, 1938)
Keywords: Récits de voyage -- Djebel Nefousa

La Tunisia e la Tripolitania dell'oggi: impressioni di viaggio, 1901-1902. - Rossi, Giustiniano (Libreria editrice Linda Rizzi-Griffini, 1902)
Keywords: Récits de voyage -- Djebel Nefousa

Nell'Africa romana: Tripolitania - Tumiati, Domenico (Fratelli Treves, 1911)
Keywords: Récits de voyage -- Djebel Nefousa

Libya italica, terreni ed acque - Vinassa de Regny, Paolo Eugenio (U. Hoepli, 1913)
Keywords: Récits de voyage -- Djebel Nefousa

Libyan photograph album, 1937 (1937)
This bound album contains 98 black and white photographs taken during a trip to Libya in 1937 by an anonymous photographer. The overall technical and artistic quality of the photographs, along with how they are presented in the album suggest a photographer of above-average skill and experience. The album is inscribed: "A. B. in memory of the May days of 1937 in Tripoli in friendship G. S. W." With the exception of the first four photographs, the album consists of images that show scenes around Libya, such as the Hotel Albergo Mehari, a camel market, Tripoli Castle, a coastal oasis, a Bedouin village, markets and bazaars. Prominent locations shown include, Tripoli, Sabratha, Leptis Magna, Zliten, and Yefren. Additionally, photographs of people, including children, locals, officials, and soldiers can be found throughout. The first four photographs in the album appear to be scenes just prior to leaving Italy, particularly the fourth photograph, which shows the skyline of Rome and has the caption, "Departing Rome April 30." All of the writing in this album is either in German or Italian. Translation and interpretation of these languages was performed using translation tools only.
Keywords: Récits de voyage -- Djebel Nefousa

Islam in Sicilia: da Alia a Nalut, le mille e una gurfa: atti della Giornata di studio con mostra fotografica : Alia, 28 giugno 1997 - Pellitteri, Antonino (Comune, 1997)
Keywords: Récits de voyage -- Djebel Nefousa

Libia Pittoresca : I Gsur berberi del Gebel Nefusa (Il Popolo del Friuli, 1939)
Keywords: Architecture -- Djebel Nefousa; Récits de voyage -- Djebel Nefousa

FTG7 A Nalut hotel - Dudovich, Marcello (1930)
Keywords: Récits de voyage -- Djebel Nefousa

In Tripolitania : Ricordi e impressioni - Lanzoni, Primo (Bollettino dell'Associazione degli Antichi Studenti Della R. Scuola Superiore di Commercio di Venezi, 1914)
Keywords: Récits de voyage -- Djebel Nefousa

Three Years in The Libyan Desert - Falls, J. C. Ewald (T. F. Unwin, 1913)
Keywords: Récits de voyage -- Djebel Nefousa

La Tripolitaine vue par un Français - Pottier, René (F. Sorlot, 1937)
Keywords: Récits de voyage -- Djebel Nefousa

An Expedition to Tripoli - Méhier de Mathuisieulx, Henri (Bulletin of the American Geographical Society, 1904)
Keywords: Récits de voyage -- Djebel Nefousa

Adventures in Tripoli: a doctor in the desert - Griffin, Ernest H. (1924)
Keywords: Bārūnī, Sulaymān al- (1870-1940); Récits de voyage -- Djebel Nefousa

Field trip guide book of the excursion to Jebel Nefusa - Burollet, Pierre-Félix (Petroleum Exploration Society of Libya, 1963)
Keywords: Récits de voyage -- Djebel Nefousa

esplorazione fra il Gebel e Socna lungo la vallata Zelita-Harara e Cabao. Notizie del Fezzan (1913) (Tripolitania - Pubblicazioni, 1913)
Keywords: Récits de voyage -- Djebel Nefousa

Excursion au Jebel Nefusa - Burollet, Pierre-Félix (Petroleum Exploration Society of Libya, 1963)
Keywords: Récits de voyage -- Djebel Nefousa

Esplorazioni e prigionia in Libia - Sforza, Ascanio Michele (fratelli Treves, 1919)
Keywords: Récits de voyage -- Djebel Nefousa